Comparison of carbon‐based nanomaterials characteristics on H13 tool steel: Vergleich der Eigenschaften Kohlenstoff‐basierter Nanomaterialien auf H13 Werkzeugstahl. Issue 3 (23rd January 2017) - Emamian, S.; Hussain, P.; Awang, M.; Arumugam, T.; Yusof, F.; Saheed, M. S. M.; Mohamed, N. M.
Abstract : As the demand to weld higher strength materials through friction stir welding (FSW) increases, the need for better non‐consumable rotating tool also increases as it has to be able to endure high frictional and thermal deformation while the work‐piece undergoes intense plastic deformation at high temperatures. Carbon‐based nanomaterials are good options to increase strength of steel. An attempt to improve the friction stir welding tool through carbon‐based coatings on H13 tool steel has been carried out. This paper highlights the characterization of the carbon‐based coatings in regard to selected coating parameters through Field emission scanning electron microscope, energy dispersive spectroscopy, Raman Spectra, and X‐Ray photoelectron spectroscopy techniques. The analysis shows presence of graphite like structures whereas Carbon Nanotubes (CNT) was observed to be grown uniformly on the surface.